Genome, transcriptome, and metabolome analyses provide new insights into the resource development in an edible fungus Dictyophora indusiata - Duan, Mingzheng; Long, Shengfeng; Wu, Xiaojian; Feng, Bin; Qin, Sunqian; Li, Yijie; Li, Xiang; Li, Changning; Zhao, Chenggang; Wang, Lingqiang; Yan, Yong; Wu, Jianming; et al. (Frontiers in Microbiology, 2023)
Dictyophora indusiata (Vent. Ex Pers.) Fisch. (DI) is an edible and medicinal fungus widely used in East Asian countries. However, during DI cultivation, the formation of fruiting bodies cannot be regulated, which leads to yield and quality losses. Moreover, researchers have not extensively evaluated the fruiting bodies of DI, leading to a waste of resources. The present study performed a combined genome, transcriptome, and metabolome analysis of DI. Using Nanopore and Illumina sequencing approaches, we created the DI reference genome, which was 67.32 Mb long with 323 contigs. We identified 19,909 coding genes on this genome, of which 46 gene clusters were related to terpenoid synthesis. Subsequent transcriptome sequencing using five DI tissues (cap, indusia, mycelia, stipe, and volva) showed high expression levels of genes in the cap, indicating the tissue's importance in regulating the fruiting body formation. Meanwhile, the metabolome analysis identified 728 metabolites from the five tissues. Mycelium was rich in choline, while volva was rich in dendronobilin; stipe had monosaccharides as the primary component, and the cap was the main source of indole acetic acid (IAA) synthesis. We confirmed the importance of tryptophan metabolism for DI fruiting body differentiation based on KEGG pathway analysis. Finally, the combined multiomics analysis identified three new genes related to IAA synthesis of the tryptophan metabolic pathway in the cap, which may regulate DI fruiting body synthesis and improve DI quality. Thus, the study’s findings expand our understanding of resource development and the molecular mechanisms underlying DI development and differentiation.